Epigenetic barrier against the propagation of fluctuating gene expression in embryonic stem cells. Issue 18 (31st August 2017) - Saito, Yuki; Kunitomi, Akira; Seki, Tomohisa; Tohyama, Shugo; Kusumoto, Dai; Takei, Makoto; Kashimura, Shin; Hashimoto, Hisayuki; Yozu, Gakuto; Motoda, Chikaaki; Shimojima, Masaya; Egashira, Toru; et al.
Abstract : The expression of pluripotency genes fluctuates in a population of embryonic stem (ES) cells and the fluctuations in the expression of some pluripotency genes correlate. However, no correlation in the fluctuation of Pou5f1, Zfp42, and Nanog expression was observed in ES cells. Correlation between Pou5f1 and Zfp42 fluctuations was demonstrated in ES cells containing a knockout in the NuRD component Mbd3 . ES cells containing a triple knockout in the DNA methyltransferases Dnmt1, Dnmt3a, and Dnmt3b showed correlation between the fluctuation of Pou5f1, Zfp42, and Nanog gene expression. We suggest that an epigenetic barrier is key to preventing the propagation of fluctuating pluripotency gene expression in ES cells. Abstract :